Refleksi Karakter Masyarakat Madura dalam Film Pendek Mata Pena: Kajian Semiotika - David Hidayat Hidayat; Bambang Yulianto; Agusniar Dian Savitri (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to describe the character of Madurese life contained in the film "Mata Pena" with a semiotic approach. The urgency of this research is to base the view that the Madurese are notlike the negative views that have been thought so far. This study uses a qualitative approach with a description technique. The data collection technique used is the technique of watching videos, noting important things, and literature as a reinforcing reference to the argument. The analysis technique used is to reduce the data according to its classification, display the data, and conclude. This study is related to the reflection of the character of the Madurese community in the film. This study uses a qualitative approach with a description technique. The data collection technique used is the technique of watching videos, noting important things, and literature as a reinforcing reference to the argument. The analysis technique used is to reduce the data according to its classification, display the data, and conclude. The results of this study are (1) The aspects of the sign are grouped in the form of denotation, connotation, and myth. In simple terms, the meaning of denotation is the depiction of the true meaning of the Madurese language into Indonesian. For the meaning of connotation and myth are two things related to the agreed meaning in the cultural life of the Madurese community. This is illustrated in the myth that contains the proverb (parebhasan) of Madura which is mutually agreed upon. (2) The reflection (character) in the short film Madura contains several characters, namely kinship, firm (steadfast), careful, and trustworthy. These characters are the implementation of Madurese culture in daily social life.